Computer-designed orthogonal RNA aptamers programmed to recognize Ebola virus glycoproteins - Yue Teng; Shuxia Liu; Shan Yang; Xiaocan Guo; Yanwen Zhang; Yajun Song; Yujun Cui (Elsevier, 2019)
Ebola virus (EBOV), a member of the filovirus family, is an enveloped negative-sense RNA virus that causes lethal infections in humans and primates. Thousands of people have died from the Ebola virus disease (EVD) in West Africa, and no specific antiviral medication and treatment have been approved for EVD. Although the development of an EBOV vaccine is promising, immunity to any vaccine is not immediate. Here, we computationally analysed the structure of EBOV glycoprotein GP2 (GP2EBOV) and designed RNA aptamers that recognize and inhibit it. The aptamers specifically bind to conserved arginine residues (Arg587 and Arg596) located in the C-terminal coiled-coil region of GP2EBOV. Molecular docking of the synthetic RNA aptamers with the ectodomain of GP2EBOV revealed that the optimized orthogonal RNA aptamers have strong binding affinities with the coiled-coil region of GP2EBOV. The characterized RNA aptamers may facilitate strategies to block replication of EBOV and related Filoviruses, and thus may serve as important antivirals to reduce mortality associated with these infections.